2005
DOI: 10.1681/asn.2004090804
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Existing Glomerulosclerosis by Inhibition of Aldosterone

Abstract: In this study, the effects of inhibition of aldosterone on regression of existing hypertension-related glomerulosclerosis were investigated. Adult male Sprague Dawley rats (220 to 250 g) underwent 5/6 nephrectomy (Nx). Severity of glomerulosclerosis was assessed by renal biopsy 8 wk later, and rats were divided into four groups with equal biopsy sclerosis and then randomized by group to 4-wk treatments as follows: Control with no further treatment (CONT; n ‫؍‬ 6); spironolactone (SP) alone (200 mg/kg per d, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 56 publications
5
124
0
4
Order By: Relevance
“…24 We also demonstrated the modulation of adrenomedullin expression in response to various injurious stimuli in cultured podocytes. 27 Furthermore, a recent article by Aldigier et al 44 indicates the role of aldosterone in podocyte injury seen in a rat model of renal ablation. Thus, podocytes in DSHs might be injured by mechanical stress, oxidative stress, and/or vasoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…24 We also demonstrated the modulation of adrenomedullin expression in response to various injurious stimuli in cultured podocytes. 27 Furthermore, a recent article by Aldigier et al 44 indicates the role of aldosterone in podocyte injury seen in a rat model of renal ablation. Thus, podocytes in DSHs might be injured by mechanical stress, oxidative stress, and/or vasoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, MR antagonists markedly ameliorated glomerular and/or tubulointerstitial injury in several models of nephropathy, including spontaneously hypertensive strokeprone rats (50,51), angiotensin II and NO synthase inhibitortreated rats (52), aldosterone-treated rats (25), and in a ureteral obstruction model (66). Moreover, Aldigier et al (2) reported that MR blockade not only reduced the development of glomerulosclerosis but also induced regression of existing glomerulosclerosis in rats after 5/6 nephrectomy. In humans, pilot studies showed that the addition of spironolactone to angiotensin-converting enzyme inhibitors had no hemodynamic effects but markedly reduced proteinuria in patients with renal failure (8) and in patients with type 2 diabetes (53).…”
Section: Invited Reviewmentioning
confidence: 99%
“…Animal studies have shown that aldosterone has an independent role in the development of hypertensive nephropathy and vascular injury resulting in myocardial and renal fibrosis, and its blockade reduces proteinuria (12)(13)(14)(15)(16). In humans, RAS blockade with ACEi or ARB results in an incomplete suppression of serum aldosterone levels, a phenomenon known as "aldosterone escape" (17).…”
mentioning
confidence: 99%